Tantangan Implementasi AI di Perbankan Syariah: Perspektif Regulasi dan Etika - Safriatullah, Safriatullah; Auliadi, Rizki; Amrullah, Amrullah; Nurmalawati, Nurmalawati; Jais, Muhammad (Jurnal Ilmiah Guru Madrasah, 2025)
The rapid advancement of artificial intelligence (AI) technology has fundamentally transformed the banking industry, including the Islamic banking sector, which faces its own distinct challenges. The adoption of AI in Islamic banking requires not only efficiency and innovation but also strict adherence to Shariah principles derived from the Qur’an and Hadith, such as the prohibitions against riba, gharar, and maysir. This article aims to provide an in-depth analysis of the regulatory and ethical challenges associated with the implementation of AI in Islamic banking. Employing a literature-based qualitative approach with thematic content analysis, this study examines recent academic sources, focusing on legal frameworks, algorithmic transparency, customer data usage, and the validation of Shariah compliance. The findings reveal significant regulatory gaps across different jurisdictions, particularly regarding explainability, privacy protection, and the accountability of AI-driven decisions. Moreover, Islamic ethical considerations—such as justice, public interest, and trustworthiness—underscore the need for the comprehensive integration of Shariah values into AI governance. This article proposes a conceptual framework for Shariah-compliant AI governance, emphasizing collaborative efforts among regulators, Islamic financial institutions, and technology providers, and highlights the importance of a “Shariah Compliance by Design” approach to safeguard the integrity of Islamic principles amid the digital transformation of the banking industry. Abstrak Perkembangan pesat teknologi kecerdasan buatan (AI) telah membawa perubahan mendasar dalam industri perbankan, termasuk pada sektor perbankan syariah yang menghadapi dinamika tersendiri. Penerapan AI di perbankan syariah bukan hanya menuntut efisiensi dan inovasi, melainkan juga harus sejalan dengan prinsip-prinsip syariah yang bersumber dari Al-Qur’an dan Hadits, seperti larangan riba, gharar, dan maysir. Artikel ini bertujuan untuk mengkaji secara mendalam tantangan regulasi dan etika yang muncul dalam implementasi AI di industri perbankan syariah. Penelitian menggunakan metode studi pustaka dengan analisis konten tematik terhadap literatur akademik terkini, berfokus pada aspek kerangka hukum, transparansi algoritma, penggunaan data nasabah, dan validasi kepatuhan syariah. Hasil analisis menunjukkan masih adanya kesenjangan regulasi yang signifikan di berbagai yurisdiksi, khususnya terkait prinsip explainability, perlindungan privasi, serta akuntabilitas keputusan berbasis AI. Selain itu, aspek etika Islam seperti keadilan, kemaslahatan, dan amanah menuntut integrasi nilai-nilai syariah secara menyeluruh dalam tata kelola AI. Artikel ini menawarkan kerangka konseptual untuk tata kelola AI yang berbasis pada kolaborasi regulator, institusi keuangan syariah, dan perusahaan teknologi, serta menekankan pentingnya pendekatan “Shariah Compliance by Design” guna menjamin integritas prinsip syariah dalam transformasi digital perbankan syariah.